Automatic processing of natural-language electronic texts with NooJ : 9th International Conference, NooJ 2015, Minsk, Belarus, June 11-13, 2015, Revised selected papers /: 9th International Conference, NooJ 2015, Minsk, Belarus, June 11-13, 2015, Revised selected papers. (2016) - Unknown
No abstract available